2020
DOI: 10.14569/ijacsa.2020.0110425
|View full text |Cite
|
Sign up to set email alerts
|

Predict Students’ Academic Performance based on their Assessment Grades and Online Activity Data

Abstract: The ability to predict students' academic performance is critical for any educational institution that aims to improve their students' learning process and achievement. Although students' performance prediction problem is studied widely, it still represents a challenge and complex issue for educational institutions due to the different features that affect students learning process and achievement in courses. Moreover, the utilization of web-based learning systems in education provides opportunities to study h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Alhassan et al [15] proposed a study of analyzing student learning behaviors and predicting their academic performance in web-based learning management systems (LMS). The study observed the student learning patterns on the online study platform using five machine learning classifiers: J48 of decision tree, random forest (RF), the logistic regression (LR), sequential minimal optimization (SMO), and multilayer perceptron (MLP).…”
Section: A Feature Selection Methods and Prediction Models In Edmmentioning
confidence: 99%
See 3 more Smart Citations
“…Alhassan et al [15] proposed a study of analyzing student learning behaviors and predicting their academic performance in web-based learning management systems (LMS). The study observed the student learning patterns on the online study platform using five machine learning classifiers: J48 of decision tree, random forest (RF), the logistic regression (LR), sequential minimal optimization (SMO), and multilayer perceptron (MLP).…”
Section: A Feature Selection Methods and Prediction Models In Edmmentioning
confidence: 99%
“…Accuracy and root mean square error are the two commonly used metrics evaluating predction models. www.ijacsa.thesai.org  Accuracy (ACC): ACC is a common model evaluation metric used to evlauce the performance of prediction model by computing the percentage of coreectly prediction [15]. It is calculated as in (1).…”
Section: Model Evaluation Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase 2 involved two parts. The first part was the building, training, and testing of ensemble-based models by using Bagging (BAG), Random SubSpace (RNDS), MultiClass Classifier (MCC), and Rotation of Forest (ROF) Algorithms [15]. The second part was the building, training and testing of the base learner or classification-based models using Naïve Bayes (NB), MultiLayer Perceptron (MLP), k-Nearest Neighbour (KNN), and Decision Table (DT) algorithms.…”
Section: B Phase 2 -Train Models Without Hybridisationmentioning
confidence: 99%